2020
DOI: 10.9734/ejmp/2020/v31i830263
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey of Medicinal Plants Used in the Treatment of Cough in Akinyele Local Government Area, Oyo State, Nigeria

Abstract: Majority of people in developing countries rely on Traditional Medical Practitioners (TMPs) or herbalist, hunters and community elders for the treatments of various diseases and illness due to their vast knowledge of medicinal plant usage. There is need to protect the flora and fauna and also the knowledge database often stored in the memories of elders, ancestral and traditional healers. Ethnobotanical study of medicinal plants used in the treatment of cough was carried out in Akinyele Local Government with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…However, it was observed in this study that the plant species were used either fresh or dry in the preparation of recipes. This agreed with the findings of Ariyo et al (2020a) and Kwon-Ndung et al (2018).…”
Section: Mode Of Preparation Of Recipessupporting
confidence: 93%
See 1 more Smart Citation
“…However, it was observed in this study that the plant species were used either fresh or dry in the preparation of recipes. This agreed with the findings of Ariyo et al (2020a) and Kwon-Ndung et al (2018).…”
Section: Mode Of Preparation Of Recipessupporting
confidence: 93%
“…In a study conducted by Erhenhi et al (2016) in Edo State, Nigeria, trees provided the highest proportion of plants at 52.38% in the treatment of skin diseases followed by herbs at 33.33% and shrubs at 14.29%. According to Ariyo et al (2020a) and (2020b), trees were found to be the most cited category in the treatment of cough and pile. Also, Malik et al (2019) found trees (38%) as mostly utilized in the treatment of various ailments and disorders, followed by herbs (30%), shrubs (22%), climbers (5%) and grass species (5%).…”
Section: Life Forms Of Medicinal Plantsmentioning
confidence: 99%
“…This means that more people had access to electronic media (radio and television) and there was a wider media coverage on the ban on logging. This findings is in line with the view of [14], who stated that the media remained an important instrument for disseminating agricultural information, especially to rural areas. Most respondents (31.4, 25.7 and 11.5 percent) from forest communities, timber dealers and NGOs also got information on the ban through the actions (patrols and arrests) of the antideforestation taskforce, whose high handedness were often directed at poor, small-scale timber dealers, a situation which corroborate with the findings of [7], when he stated that most bans on logging are effective only on small-scale commercial loggers.…”
Section: Awareness and Reasons For The Ban On Loggingsupporting
confidence: 90%
“…In Morocco, the infusion so used in the management of respiratory . The fresh root of ginger in Oyo State Nigeria is popularly used for the treatment of cough [34]. In a Southern State in Nigeria, the juice is used for the management of hypertension, as laxative, ant catarrh.…”
Section: Medicinal Usesmentioning
confidence: 99%